2022
DOI: 10.1016/j.molmet.2021.101400
|View full text |Cite
|
Sign up to set email alerts
|

Ups and downs: The PPARγ/p-PPARγ seesaw of follistatin-like 1 and integrin receptor signaling in adipogenesis

Abstract: Objective Although Follistatin-like protein 1 (FSTL1), as an “adipokine”, is highly expressed in preadipocytes, the detail role of FSTL1 in adipogenesis and obesity remains not fully understood. Methods In vitro differentiation of both Fstl1 −/− murine embryonic fibroblasts (MEFs) and stromal vascular fraction (SVF) were measured to assess the specific role of FSTL1 in adipose differentiation. Fstl1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
(56 reference statements)
1
11
0
Order By: Relevance
“…Follistatin-like 1 (FSTL1) is a novel pro-inflammatory cytokine that is ~37 kDa in size and is highly expressed in AT, and mainly in the stromal vascular fraction 121 ). Moreover, FSTL1 expression is high in preadipocytes with a transient upregulation in early differentiated cells and then declines to basal levels after differentiation ( 121 123 ). Hence, FSTL1 has a potential role in adipogenesis.…”
Section: Adipokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Follistatin-like 1 (FSTL1) is a novel pro-inflammatory cytokine that is ~37 kDa in size and is highly expressed in AT, and mainly in the stromal vascular fraction 121 ). Moreover, FSTL1 expression is high in preadipocytes with a transient upregulation in early differentiated cells and then declines to basal levels after differentiation ( 121 123 ). Hence, FSTL1 has a potential role in adipogenesis.…”
Section: Adipokinesmentioning
confidence: 99%
“…Hence, FSTL1 has a potential role in adipogenesis. Indeed, a recent study found that FSTL1 deficiency inhibited preadipocyte differentiation in vitro and obesity development in vivo ( 123 ). In addition, FSTL1 has been shown to act as a novel stimulator of β-adrenergic signaling and promote BAT thermogenesis ( 124 ).…”
Section: Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 During the switch from chow diet to high fat diet (HFD), FSTL1 deletion mice gained less body weight, fat mass, and glucose level than the control group. FSTL1 promoted adipogenesis by inhibiting the conversion of PPARγ to p-PPARγ through the integrin/FAK/ERK signaling pathway, 9 and could activate NFκB and JNK signaling pathways, critical in obesity-induced inflammation and IR, in adipocytes and macrophages. 8 Insulin-stimulated phosphorylation of both Akt and IRS-1 was markedly reduced by FSTL1 treatment, which impaired insulin signal transduction in 3T3-L1 adipocytes.…”
Section: Pro-inflammatory Adipokinesmentioning
confidence: 99%
“…We showed that both high levels of FSTL1 at the onset and its subsequent reduction during the process are required for normal differentiation in this cell line [13]. Importantly, in vivo experiments by others confirmed that differentiation to adipocytes of Fstl1-/- mouse embryonic fibroblasts (MEFs) and stromal vascular cells (SVCs) was impaired [14]. Moreover, different reports are starting to link FSTL1 with obesity in humans (see for example [15, 16]).…”
Section: Introductionmentioning
confidence: 99%